2010
DOI: 10.1007/s10029-009-0614-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Repair technique of sportsmen’s groin: an innovative open-suture repair to treat chronic inguinal pain

Abstract: The Minimal Repair technique is an effective and safe way to treat sportsmen's groin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 26 publications
2
74
0
3
Order By: Relevance
“…Read, a senior herniologist, has frequently used 'herniology' as a title word in his publications [5,6]. Today, evidence shows better surgical outcomes occur with specific hernia surgeons and centres, with no formal certifications programmes yet [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Read, a senior herniologist, has frequently used 'herniology' as a title word in his publications [5,6]. Today, evidence shows better surgical outcomes occur with specific hernia surgeons and centres, with no formal certifications programmes yet [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In a number of papers the importance of coexisting adductor tendinosis in patients with sports hernia is noted. In other papers coexistence of nerve entrapment neuralgia with sports hernia is also acknowledged [13,16,20]. A study conducted by Ekstrand and Hilding studying more than 300 soccer players found the majority of injured patients had more then one potential cause of pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature and our study, treatment of patients with chronic groin pain is complex and surgery has a role. It enables faster recovery and return to sports [5,16,20]. Reinforcement of the posterior wall is necessary in the majority of patients after performing physical examination and dynamic ultrasound for signs of occult hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muschaweck [ 54 ] minimal repair -Opening of the posterior inguinal wall only at the area of the defect (intact structures remain intact), Suture line over the pubic bone (tension of the Rectus muscle is reduced), Conservation of sliding mobility of the abdominal wall.…”
Section: Muschaweckmentioning
confidence: 99%